VARIABILITY ON GROUPERS SPECIES COMPOSITION AND SIZE AT ALAS STRAIT WATERS - Ratna Ayu Istiani; Soraya Gigentika; Ayu Adhita Damayanti; Benaya Meitasari Simeon (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
Alas Strait is the one of the main coral reef fishing grounds in West Nusa Tenggara (WNT generating high economic value for coastal communities, particularly through grouper (Epinephelidae) fisheries. This area is also designated as a provincial priority zone for coral reef fish resource management. This study aimed to describe the variability in species composition and length distribution of groupers caught by local fishers operating in the Alas Strait. Field survey were conducted in May–June 2024 and February 2025 using direct measurement and interview methods. Grouper samples were obtained from fishers’ catches in the Alas Strait and from the Tanjung Luar Fish Market using accidental sampling and fishers recruited using snowball sampling. Data were analyzed to characterise species composition structure and length-frequency distribution. This research showed 36 grouper species in total recorded from fishers’ catches in the Alas Strait during the study period. The most dominant species were Epinephelus fasciatus (25.47%), Epinephelus coioides (7.87%), Epinephelus areolatus (6.74%), and Epinephelus ongus (6.74%). Length distribution indicated E. fasciatus and E. ongus were predominantly caught at the mature gonadal stages, while E. coioides and E. areolatus were mostly captured in the immature stages. Key words: fish length distribution, Epinephelus sp., gonadal maturity, Tanjung Luar